The Hidden Struggle: Review of Obsessive-Compulsive Disorder (OCD) Among Athletes - Korol-Borodziuk, Aleksander; Karolak, Dominika; Białowąs, Tymoteusz; Lauko, Kamil; Nowicka, Iga; Macko, Angelika; Łuniewski, Bartosz (Quality in Sport, 2026)
Background. Obsessive-Compulsive Disorder (OCD) is a common mental health disorder, often associated with significant psychological stress and functional impairment [1]. It is characterized by the presence of intrusive, uncontrollable thoughts or urges (obsessions), alongside repetitive, excessive behaviours or mental acts (compulsions) performed in an attempt to reduce anxiety or prevent perceived harm [1]. Aim. This research article aims to discuss the prevalence, manifestations, impact and treatment of OCD among athletes. Materials and methods. A targeted review of relevant literature was carried out using the PubMed database, using the following search times: “Obsessive Compulsive Disorder”; “physical activity”; “treatment”. Summary. The article highlights how Obsessive-Compulsive Disorder (OCD) in athletes can often go unnoticed, largely because perfectionism and ritualistic behaviours are so common—and even celebrated—in sports culture. For many athletes, obsessive thoughts may center around fears of failing, getting injured, or becoming contaminated. In response, they might engage in compulsive behaviours like rigid training routines, strict superstitions, or repeated pre-performance rituals. Cognitive Behavioural Therapy (CBT), especially a method called Exposure and Response Prevention (ERP), is considered the most effective treatment for OCD. However, when working with athletes, therapists may need to tailor their approach to better fit the unique pressures and routines of sports life. Conclusions. OCD poses unique challenges in sports medicine, where the line between discipline and dysfunction is often blurred and difficult to distinguish. Early detection, targeted, and tailored interventions are key to maintaining both mental health and athletic performance. Further research is needed to clarify prevalence rates, develop sports-specific screening tools, and assess the effectiveness of modified treatment protocols for this population.